Blue Carbon Storage Capacity of Temperate Eelgrass (Zostera marina) Meadows. Issue 10 (8th October 2018) - Röhr, Maria Emilia; Holmer, Marianne; Baum, Julia K.; Björk, Mats; Chin, Diana; Chalifour, Lia; Cimon, Stephanie; Cusson, Mathieu; Dahl, Martin; Deyanova, Diana; Duffy, J. Emmet; Eklöf, Johan S.; et al.
Abstract: Despite the importance of coastal ecosystems for the global carbon budgets, knowledge of their carbon storage capacity and the factors driving variability in storage capacity is still limited. Here we provide an estimate on the magnitude and variability of carbon stocks within a widely distributed marine foundation species throughout its distribution area in temperate Northern Hemisphere. We sampled 54 eelgrass ( Zostera marina ) meadows, spread across eight ocean margins and 36° of latitude, to determine abiotic and biotic factors influencing organic carbon (Corg ) stocks in Zostera marina sediments. The Corg stocks (integrated over 25‐cm depth) showed a large variability and ranged from 318 to 26, 523 g C/m 2 with an average of 2, 721 g C/m 2 . The projected Corg stocks obtained by extrapolating over the top 1 m of sediment ranged between 23.1 and 351.7 Mg C/ha, which is in line with estimates for other seagrasses and other blue carbon ecosystems. Most of the variation in Corg stocks was explained by five environmental variables (sediment mud content, dry density and degree of sorting, and salinity and water depth), while plant attributes such as biomass and shoot density were less important to Corg stocks. Carbon isotopic signatures indicated that at most sites <50% of the sediment carbon is derived from seagrass, which is lower than reported previously for seagrass meadows. The high spatial carbon storage variability urges caution in extrapolating carbon storage capacity between geographical areas as well as within and between seagrass species. Key Points: The Z. marina Corg stocks varied widely within and across studied regions; majority of this variation was explained by five sediment and environmental variables The Z. marina Corg stocks were comparable to other seagrass species and other blue carbon habitats such as salt marshes and mangrove forests Carbon isotopic signatures indicated that at most sites, only less than half of the sediment carbon is derived from seagrass, though variation was significant